A simple statistical model and physical device to estimate a woman-specific probability of skilled birth assistance and associated benefit of maternity waiting home stay - Jérémie Gallien; Qi George Chen; Yuhang Du; Yi Zhang; Jody Lori; Joseph Sieka; Bentoe Tehoungue (PLoS ONE, 2025)
This paper presents a simple mathematical model and an associated physical device to predict (i) the risk that a woman’s active labour will begin without a skilled birth attendant based on her parity and anticipated time to access skilled care; and (ii) the extent to which that risk may be reduced by moving to a maternity waiting home some time before her expected due date. This tool is designed to facilitate more systematic discussions and better-informed decisions about labour care access arrangements during antenatal consultations.